WE HAVE ONE UKRAINE AND ONE LANGUAGE! - Лесюк, М. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Mykola Lesiuk’s article “We have one Ukraine and one language” deals with the demeaning state of the Ukrainian language in the modern Ukrainian society. In spite of the official status of the Ukrainian language, it is ignored in the official sphere, on television and in the other mass media, giving all the preference to Russian. The reason of such a status is an insufficient attention to the language on the side of the country’s authorities. The language is a major attribute of the nation, a major means of uniting people, however, the division of Ukrainians into Ukrainianphone and Russianphone, constantly supported by the power, doesn’t promote such a unity.